Handbook of flavour ingredients - Burdock, George A. (CRC Press LLC, 2011)
Updated to reflect the latest data, Fenaroli's Handbook of Flavor Ingredients, Fifth Edition is the newest edition of an industry standard. It features more than 100 newly designated GRAS substances, expanded information on aroma and taste thresholds, and the most current regulatory information. It includes synonyms, international codes, sensory and organoleptic information, permitted uses of ingredients, international regulations, and more. The handbook is designed to be the most current resource on GRAS and non-GRAS flavoring substances for flavor chemists, food scientists, food safety and quality control personnel, and professionals in the pharmaceutical, dietary, and cosmetics industries.